Penerapan Permainan Teka-Teki Silang Untuk Meningkatkan Kompetensi Bahasa Arab Tingkat SMP - Adinda robi'atul Adawiyah; Farikh Marzuki (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
Education in Indonesia has an important role in advancing the quality of human resources. In order to achieve this goal, it is necessary to provide variations in learning media so that students are active so that learning becomes effective. This research aims to improve the mastery of Arabic vocabulary for class VII SMP NU HASYIM ASY' ARI SEDATI SIDOARJO. Therefore, this research applies the crossword puzzle game as media. This type of research is Classroom Action Research (PTK). This Classroom Action Research was carried out in two cycles, each cycle had four planning stages, namely data collection, data reduction, data presentation, and drawing conclusions. This research was carried out at SMP NU HASYIM ASY'ARI SEDATI SIDOARJO and the research subjects this time were 39 class VII students. This research was carried out during the odd semester of the 2023/2024 academic year. This research was conducted using 2 cycles. Cycle 1 was carried out on Monday 07 August 2023 with a percentage gain of 24%. Cycle 2 was carried out on Monday 28 August 2023 with a percentage gain of 87%. From the comparison of the two cycles, there is a very significant increase of 63%. It is proven that increasing the use of crossword puzzle game media is very effective.